Kajian Literatur: Faktor Yang Berpengaruh Terhadap Keputusan Investasi Mahasiswa (Lembaga Pengembangan Kinerja Dosen, 2023)
The increasing investment activities in Indonesia have encouraged most students to start their involvement in the world of investment. Students make investments with the aim of gaining profits in the present and future. Of course, students need to make investment decisions carefully and pay attention to the factors that influence investment decisions. The purpose of this paper is to identify the factors that influence students' decision making in investing. This research uses the literature review method. In this literature review process, the author analyzes a number of journal articles that discuss the factors that influence students' investment decisions. Relevant journal articles were selected after searching for research sources through Google Scholar. The reference sources used are accredited national journals. From the results of the literature review analysis of several related journal articles, it can be concluded that student investment decisions are influenced by several factors. Factors that support students in making investment decisions are financial literacy, demographic factors, risk tolerance, risk perception, investment knowledge, overconfidence, and herding.